Retraction Note: The Importance of Religion, Spirituality, and Spiritual Care in Patients with Multiple Sclerosis - Çaksen, Hüseyin (Journal of Pediatric Neurology, 2024)
The above article published in Journal of Pediatric Neurology on May 22, 2023 (DOI: 10.1055/s-0043-1768656), has been retracted as it is lacking scientific base.